2011
DOI: 10.1159/000328456
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in High Human Chorionic Gonadotropin in Twin-Twin Transfusion Syndrome following Fetoscopic Laser Surgery

Abstract: Introduction: The purpose of this study was to investigate the concentration of maternal serum human chorionic gonadotropin (hCG) in twin-twin transfusion syndrome (TTTS) before and after fetoscopic laser surgery and to clarify the association between TTTS and hCG. Material and Methods: The concentration of maternal serum hCG was measured before fetoscopic laser surgery and 2 and 4 weeks after laser surgery in 120 patients diagnosed with TTTS. Results: The preoperative serum concentration of hCG was 6.34 multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The most likely mechanisms are the large placental volume and placental hypoxia secondary to uteroplacental blood flow disruption by the polyhydramnios surrounding the recipient fetus (8). Successful treatment of TTTS with FLC of placental vascular anastomoses led to decrease and then normalization of hCG levels by 2 and 4 weeks, respectively (11). The observations in the present case are consistent with these data.…”
Section: Discussionsupporting
confidence: 89%
“…The most likely mechanisms are the large placental volume and placental hypoxia secondary to uteroplacental blood flow disruption by the polyhydramnios surrounding the recipient fetus (8). Successful treatment of TTTS with FLC of placental vascular anastomoses led to decrease and then normalization of hCG levels by 2 and 4 weeks, respectively (11). The observations in the present case are consistent with these data.…”
Section: Discussionsupporting
confidence: 89%
“…However, this review included both selective and non‐selective FLP and these fetoscopic techniques are associated with differing rates of recurrence. Furthermore, since 2007, several authors have reported outcomes following SFLP for TTTS. Here we present a systematic review of the incidence and management of recurrent TTTS after SFLP.…”
Section: Introductionmentioning
confidence: 99%
“…The laser therapy was performed as described in a previous report [15]. We excluded the some cases in which a single or double fetal death occurred after laser therapy, and recurrent cases of TTTS with polyhydramnios/oligohydramnios, because fetal death itself can lead to a decrease in hCG, and the recurrence of TTTS did not cause a decrease in hCG, as has been previously reported [9].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that elevated maternal serum hCG is seen in TTTS, and that there is a close association between hCG elevation and TTTS [8]. The change in the value of hCG after laser therapy may be a marker of laser therapy efficacy [9].…”
Section: Human Chorionicmentioning
confidence: 98%